2013
DOI: 10.1038/ejhg.2013.237
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic outcomes of three-way translocations ascertained in cleavage-stage embryos: refinement of reproductive risks and implications for PGD

Abstract: Our study provides an analysis of the outcome of meiotic segregation of three-way translocations in cleavage-stage embryos and the accuracy and limitations of preimplantation genetic diagnosis (PGD) using the fluorescence in situ hybridization technique. We propose a general model for estimating reproductive risks for carriers of this class of complex chromosome rearrangement. The data presented describe six cycles for four couples where one partner has a three-way translocation. For male heterozygotes, 27.6% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…The advent of efficient techniques for fast in situ chromosomal detection and precise genome analysis has contributed to improve our understanding of CCR formation and etiology (3,4). Today, several laboratories propose preimplantation genetic diagnosis (PGD) procedures for couples with CCRs, thus offering an alternative to prenatal diagnosis and pregnancy termination (5)(6)(7)(8). The occurrence of CCRs also constitutes a feature of numerous cancers (9).…”
mentioning
confidence: 98%
“…The advent of efficient techniques for fast in situ chromosomal detection and precise genome analysis has contributed to improve our understanding of CCR formation and etiology (3,4). Today, several laboratories propose preimplantation genetic diagnosis (PGD) procedures for couples with CCRs, thus offering an alternative to prenatal diagnosis and pregnancy termination (5)(6)(7)(8). The occurrence of CCRs also constitutes a feature of numerous cancers (9).…”
mentioning
confidence: 98%
“…E. Vanneste et al reported a couple in which the husband was an exceptional CCRs carrier with two PGT cycles, who had 4 balanced or normal embryos and 12 abnormal embryos [14] . Paul et al reported 4 couples, including 3 males and 1 female three-way rearrangements carriers with 6 PGT cycles, who had 6 euploid embryos and 31 aneuploid embryos [10] . Hu L et alreported 7 couples, including 5 couples with three-way rearrangements, who 6 had 3 balanced or normal embryos, 31 abnormal embryos and one embryo of amplification failure, and 1 couple with double two-way translocations, who had no balanced or normal embryos and 12 abnormal embryos [1] .…”
Section: Embryo Identification Of the Pgt Cycles For Bccr Couplesmentioning
confidence: 99%
“…Therefore, recurrent spontaneous abortion, arrested intrauterine pregnancy (aIUP), fetal malformation and infertility often happen. In addition, male BCCR can also be observed as oligoasthenoterazoospermia and infertile [7,10] . It has been reported that the odds of balanced or normal embryos in couples with BCCR are <6% [1] .Preimplantation genetic testing(PGT) is performed before embryo transfer, and a small portion of cells will be aspirated for comprehensive chromosome screening to analyze embryos identified as balanced or normal for transplantation.…”
mentioning
confidence: 99%
“…Constitutional complex chromosomal rearrangements (CCRs) are relatively rare events [e.g., Berend et al, 2002;Scriven et al, 2014] that typically involve 2 or more chromosomes with at least 3 breakpoints and can result in normal or abnormal phenotypes depending on whether they entail imbalances, disrupt coding or regulatory regions, or somehow disturb the euchromatic neighborhood [Fukami et al, 2017]. CCRs often arise through well-known errors in replication or recombination that ultimately lead to the "accumulation" of DNA defects.…”
Section: © 2019 S Karger Ag Baselmentioning
confidence: 99%
“…Familial CCRs often represent a challenge for genetic counseling since each rearrangement and its segregation are unique, leading to distinct reproductive risks for carriers. Healthy carriers with impaired reproduction might transmit the balanced CCR which may lead to an unbalanced karyotype [Pellestor et al, 2011, Rivera andDominguez, 2012;Scriven et al, 2014;Tulay et al, 2015]. Such imbalances may occur in one or more of the rearranged chromosomes and lead to phenotypes specific to one or more syndromes or unspecific phenotypes [e.g., Neira et al, 2012;Rivera and Dominguez, 2012].…”
Section: © 2019 S Karger Ag Baselmentioning
confidence: 99%